Sistem Informasi Layanan Pengaduan Inventarisasi Jalan Berbasis Website - Widyaningrum, Shiska Wahyu; Alfianti, Pramesti Gita; Irianti, Faizah; Siswanto, Joko (Proceedings Series on Physical & Formal Sciences, 2023)
There was a lot of damage to road equipment facilities that were no longer functioning. There are public complaints about the condition of damaged roads which seem to be ignored because of the unavailability of effective facilities for the community and government in dealing with the problem. The need for online media to submit reports and public complaints against road equipment facilities. The development of this application is based on a website about road inventory damage complaint services. The resulting features are in the form of a menu of road equipment explanations and complaint forms accessed by users. For admins can access the feature of registering incoming reports and responding to complaints. Designed using research methods (Extreme Programming) with stages of planning, design, coding, and testing. The benefit of this application is that it makes it easier for the public to report damage to road inventory and helps stakeholders in knowing road information.